Answer:
90
Step-by-step explanation:
Answer:
1295/36
Step-by-step explanation:
the statement tell us:
(7-(5/6))*(7-(7/6))
we have:
(7-(5/6))=((6*7)-5)/6=(42-5)/6=37/6
and we have:
(7-(7/6))=((6*7)-7)/6=(42-7)/6=35/6
we need multiply both terms:
(37/6)*(35/6)=(37*35)/(6*6)
finally we have
1295/36
Answer:
$18.00
Step-by-step explanation:
8 x 1.25 = 10
8 + 10 = 18
0 = f(x) = (x - r)(x - s) = x² - (r+s) + rs
We have r=1.5+√2, s=1.5 -√2 so r+s = 3 and
rs = (1.5+√2)(1.5 - √2) = 1.5² - (√2)² = 2.25 - 2 = 0.25
f(x) = x² - 3x + -.25
For integer coefficients we mulitply by 4,
g(x) = 4f(x) = 4x² - 12x - 1
Answer: 4x² - 12x - 1 = 0
Answer:
A function is a relation in which each input has only one output. In the relation , y is a function of x, because for each input x (1, 2, 3, or 0), there is only one output y. x is not a function of y, because the input y = 3 has multiple outputs: x = 1 and x = 2.
Step-by-step explanation: